2017
DOI: 10.4103/0976-3147.193545
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction: A comparative study of patients with Alzheimer’s and frontotemporal dementia – A pilot study

Abstract: Introduction:In frontotemporal dementia (FTD) and Alzheimer's disease (AD), central autonomic structures get affected early. An insight into autonomic functions in these patients is likely to be of diagnostic importance and thus help in prognosticating and also probably explain unexplained sudden death in some of these patients.Objectives:The objective of this study is to identify autonomic dysfunction prevailing in patients. Then, if there is dysfunction, is the pattern same or different in these two conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…This observation correlates with neurochemical abnormality in AD which involves cholinergic depletion. The same information is supported by some of the previous studies [24,25].…”
Section: Discussionsupporting
confidence: 86%
“…This observation correlates with neurochemical abnormality in AD which involves cholinergic depletion. The same information is supported by some of the previous studies [24,25].…”
Section: Discussionsupporting
confidence: 86%
“…Patients with cognitive decline might have difficulties in self-care, disease management, and low compliance to medications with consequent instability in several biological parameters, increasing the possibility of reverse causation. It is also suggested that central autonomic dysfunction may accompany dementia, which could contribute to worsening of variability in BP and glucose [ 38 ]. However, our data showed a strong correlation between variability indices and dementia with a dose–response relationship, were consistent with previous data, and were coherent with laboratory findings supporting the causal relationship [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 22 tissue types with data for at least 25 cell lines each from the DepMap 2020 Q2 release which were selected for further analysis (Table 1). We speci cally highlighted results from three tissue types most relevant to AD etiology: hematopoietic and lymphoid tissue (HL, given the now established role of immune response and phagocytotic pathway in AD), central nervous system (CNS), and autonomic ganglia (AG) [16][17][18].…”
Section: Gene List and Depmap Data Assemblymentioning
confidence: 99%